From conceptual to actual design of unmanned vehicle - Ng, Alvin Heng San. (2010)
From the conceptual design selection process to the phase two prototype, a miniaturized (170mm x 105mm x 80mm) Unmanned Surveillance Ground Vehicle (USGV) is built from scraps to test its capabilities. Using the findings from the literature review, it is discovered that there is classification of vehicles which gives it different terrain capabilities.